(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
This paper is aimed to focus on bandwidth en hancement of a slot antenna with coplanar waveguide feeding. The experimentation is performed on the general CPW struc ture which is having a signal conductor in the middle and two ground layers etched on either side of feed with some gap to allow a unique feature of uniplanar in construction. In this con text, the study of a CPW transmission line discontinuity is ap plied to prepare a slot antenna and this is followed by the study of incorporating serrated shape in the structure.